2018
DOI: 10.1177/0018720818790719
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Facet Joint Kinematics and Load Effects During Dynamic Lifting

Abstract: This study provided new insights into the role of lumbar facet joints in vivo during lifting. Alterations in the facet joint kinematics due to vigorous functional demand can be one of the primary but overlooked mechanical factors in the causation of LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
2
17
2
1
Order By: Relevance
“…The cause of LDH due to FT is still unclear. Many studies have shown that the direction of the symmetric articular surface can affect the stress of facet joints [7][8]. Kim et al [9] through the nite element analysis, the simulation analysis was carried out on the lumbar FT, found under the stretching and torque, the FT model relative to the symmetry model, the pressure in the lumbar increased signi cantly, the moment an intervertebral fusion, the intervertebral disc pressure on buckling, stretching, torsional and lateral bending are signi cantly increased, increased by 98.5%, 91.2%, 75.5%, and 76.5% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of LDH due to FT is still unclear. Many studies have shown that the direction of the symmetric articular surface can affect the stress of facet joints [7][8]. Kim et al [9] through the nite element analysis, the simulation analysis was carried out on the lumbar FT, found under the stretching and torque, the FT model relative to the symmetry model, the pressure in the lumbar increased signi cantly, the moment an intervertebral fusion, the intervertebral disc pressure on buckling, stretching, torsional and lateral bending are signi cantly increased, increased by 98.5%, 91.2%, 75.5%, and 76.5% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The value of comfort can be viewed as an evaluation reference of labor intensity. Yang Feng describes the astronaut’s discomfort level by the relative relationship between the torque used by the joint and the maximum available torque of the joint [ 6 ], which is defined as the ratio of the actual torque tau and the maximum force moment max of the joints, like the followings …”
Section: Methodsmentioning
confidence: 99%
“…The most common form of low back pain is nonspecific, affecting almost all age groups [ 5 ]. However, in different occupational backgrounds, workers’ repeated bending of the spine, frequent heavy lifting, manual material handling and awkward body postures are still important factors that cause MSDs of the waist [ 6 ]. Back compressive force on the spine is believed to be a contributor to low-back pain and injury, especially at the L5/S1 intervertebral disc [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This causes lumbar facet joint osteoarthritis and Lumbar facet joint arthropathy are also believed to be the primary etiology in 15%-20% of patients with chronic low back pain [8,10,17]. Some other researches established that lifting contributes the most to the risk of low back pain [5].…”
Section: Introductionmentioning
confidence: 99%